Product Design and Value Analysis on Food Product (Case Study of Vegetable Nugget Product) - Endang Retno Wedowati; Diana Puspitasari; Fungki Sri Rejeki; Tri Rahayuningsih; Johan Paing Heru Waskito (ITEGAM-JETIA, 2025)
Processed food products that are ready to cook and ready to eat are available because of the needs of today's society, which are very practical. One of the processed food products that suit these needs is nuggets. In general, nuggets are made from animal ingredients, but in this study, a vegetable nugget product design was developed. The study's purpose was to develop a product design and analyze the value of vegetable nugget products to meet consumers' needs and desires for the availability of ready-to-eat processed food products that have health benefits. The product design developed used the Conjoint Analysis method combined with Orthogonal Design to determine the product configuration. Furthermore, a value analysis is carried out on each product configuration form based on product benefits and production costs. The product variations provided were eight product variants that combined five product attributes: shape, flavor, weight, packaging material, and packaging design. The selected product is the product that has the highest value, which is based on product benefits and production costs for each product variant.